2022
DOI: 10.3390/cells11162518
|View full text |Cite
|
Sign up to set email alerts
|

An Epigenetic Role of Mitochondria in Cancer

Abstract: Mitochondria are not only the main energy supplier but are also the cell metabolic center regulating multiple key metaborates that play pivotal roles in epigenetics regulation. These metabolites include acetyl-CoA, α-ketoglutarate (α-KG), S-adenosyl methionine (SAM), NAD+, and O-linked beta-N-acetylglucosamine (O-GlcNAc), which are the main substrates for DNA methylation and histone post-translation modifications, essential for gene transcriptional regulation and cell fate determination. Tumorigenesis is attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 535 publications
1
60
0
Order By: Relevance
“…This gene codes for the p53 protein, which is a transcription factor that prevents abnormal proliferation and division of cells ( 2 ). Recent research has found that TP53 is involved in the regulation of various types of programmed cell death (PCD), which include apoptosis ( 3 ), autophagy ( 4 , 5 ), pyroptosis ( 6 ), and ferroptosis ( 7 ), and pathways for generation of reactive oxygen species (ROS) ( 8 10 ). For example, p53 promotes apoptosis by upregulating apoptosis-related proteins in order to stabilize the organism ( 11 , 12 ).…”
Section: Tp53 and Programmed Cell Death In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…This gene codes for the p53 protein, which is a transcription factor that prevents abnormal proliferation and division of cells ( 2 ). Recent research has found that TP53 is involved in the regulation of various types of programmed cell death (PCD), which include apoptosis ( 3 ), autophagy ( 4 , 5 ), pyroptosis ( 6 ), and ferroptosis ( 7 ), and pathways for generation of reactive oxygen species (ROS) ( 8 10 ). For example, p53 promotes apoptosis by upregulating apoptosis-related proteins in order to stabilize the organism ( 11 , 12 ).…”
Section: Tp53 and Programmed Cell Death In Cancermentioning
confidence: 99%
“…(6), and ferroptosis (7), and pathways for generation of reactive oxygen species (ROS) (8)(9)(10). For example, p53 promotes apoptosis by upregulating apoptosis-related proteins in order to stabilize the organism (11,12).…”
mentioning
confidence: 99%
“…Cancer, one of the most frequent diseases worldwide, are characterized by continuous cell proliferation and dysregulation of the cell cycle. This outlines the importance of chemotherapeutic agents to the modulate cell cycle and/or apoptosis [ 102 , 103 ]. The approach for understanding means of PPAR-γ activation has gained considerable momentum in recent years which is found to be expressed in a variety of cancer cells.…”
Section: Ppar-γ Agonists In Various Diseasesmentioning
confidence: 99%
“…Biomarkers of lipid peroxidation including elevated levels of TBARS were significant significantly higher in the plasma of patients with T2D in comparison to healthy subjects [ 13 ]. Beyond its implication during the development of T2D, elevated biomarkers of lipid peroxidation have been crucial in highlighting the pathological role of oxidative stress during the pathogenesis of other conditions, including cerebral vascular disease [ 14 , 15 ], obesity-driven cancer [ 16 , 17 , 18 ], and age-related dementia [ 19 ]. Thus, it is essential to recognize antioxidant therapies as a potential strategy to combat lipid peroxidation and oxidative stress during the development of diverse chronic diseases, including T2D [ 20 ].…”
Section: Introductionmentioning
confidence: 99%